Intracranial Rosai Dorfman Disease Presented With Multiple Huge Intraventricular Masses: A Case Report - Jamali, Elena; Sharifi, Guive; Ghafouri-Fard, Soudeh; Bidari Zerehpoosh, Farahnaz; Yazdanpanahi, Mahmood; Taheri, Mohammad (Frontiers in Surgery, 2022)
Introduction: Rosai-Dorfman disease (RDD) usually is presented by painless cervical lymphadenopathy during the two first decades of life with or without extranodal involvement. Exclusive extranodal manifestation and especially CNS involvement is uncommon. The etiology remains unknown and definitive diagnosis is based on characteristic histopathological and immunohistochemical features showing S100 +/ CD1a - RDD type histiocytes with emperipolesis. Most CNS cases are Dural-based masses. Case presentation: Herein, we present a case of RDD in an 8- year- old boy presenting with multiple huge intraventricular masses. Conclusion: Regarding the rarity of CNS involvement and lack of established evidence-based therapeutic approaches, reports of any individual case can supply further beneficial data concerning treatment approaches and the long-term effectiveness of therapeutic strategies.